2022
DOI: 10.1177/01945998221105059
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi Sarcoma of the Larynx: A Systematic Review

Abstract: Objective Kaposi sarcoma (KS) of the larynx is a rare disease with few cases reported in the literature. This study aims to provide a comprehensive review of laryngeal KS, including patient characteristics, treatment, and clinical outcomes. Data Sources PubMed, CINAHL, SCOPUS, and Cochrane Library. Review Methods A systematic review of the published English literature was conducted. An electronic search and bibliographic examination of articles pertaining to laryngeal KS were performed. Demographic data, tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…It is uncommonly encountered in non-immunocompromised patients, and there are few reported cases of laryngeal involvement [ 13 ]. A recent study reported 77 published cases of laryngeal KSs worldwide [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is uncommonly encountered in non-immunocompromised patients, and there are few reported cases of laryngeal involvement [ 13 ]. A recent study reported 77 published cases of laryngeal KSs worldwide [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visceral involvement of AIDS-related Kaposi sarcoma is uncommon, and laryngeal involvement without cutaneous lesions rarely occurs. To our knowledge, a recent systematic review found only 77 published case reports of Kaposi sarcoma of the larynx, predominantly in males and mostly arising in the supraglottic region [ 2 ]. The presenting symptoms can range from hoarseness of voice, which was the presenting symptom in this patient, and dysphagia to stridor or complete airway obstruction [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although AIDS-related Kaposi sarcoma involves the head and neck, the primary laryngeal disease is uncommon [ 1 ]. A literature review showed only a handful of Kaposi sarcoma cases, approximately 77 to date, affecting the larynx [ 2 ].…”
Section: Introductionmentioning
confidence: 99%